Speech Patterns in Various Song Genres (Pop, Jazz, Dangdut, Rock and Malay) - Rusdiansyah Rusdiansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study discusses the forms of speech and communicative functions found in various song genres such as in Pop, Jazz, Rock, Dangdut, and Malay songs. This research was conducted to determine whether each genre has the same or different communicative function patterns. The speech act on this song is one way of conveying the message desired by the songmaker who is expected to have the desired effect. The research method and approach used in this study is a qualitative descriptive method. Where the song lyrics as research data will be determined and described the communicative function form of each speech in the song lyrics based on Searle's theory. after that, the communicative function form will be compared in each genre of song. The method and approach are used because the data in this study are in the form of speech in each song genre. There are five song genres used as research subjects, namely Pop, Jazz, Rock, Dangdut, and Malay. The results of the research conducted showed that the speech patterns that exist in the song genre have different communicative functions. Songs that should have expressive communicative functions, but from the data analysis that has been done above prove that the songs no longer only have an expressive communicative function. In fact, from the data above, assertive functions are more commonly found, namely dominating in Pop, Malay and Jazz genre songs. Rock genre song is more dominated by the communicative function of the directive. While the expressive function that should dominate the song only dominates the Dangdut genre song.